Adrenal insufficiency as the first clinical manifestation of the primary antiphospholipid antibody syndrome. - Satta, M; Corsello, S; Della Casa, S; Rota, C; Pirozzi, B; Colasanti, S; Cina, G; Grossman, AB; Barbarino, A (2000)
We describe a 60-year-old man who developed clinical symptoms and signs of Addison's disease, which was subsequently confirmed biochemically; no cause was apparent. Several months later the patient represented with a fit, followed by a large and extensive venous thrombosis in the right iliac vein and in the veins of the right leg. He had strongly positive antibodies to cardiolipin, strongly suggesting a diagnosis of primary antiphospholipid syndrome. While Addison's disease is a well-recognized, albeit rare, manifestation of the antiphospholipid syndrome, the Addison's disease preceded other clinical evidence of the syndrome by several months, in our patient, at variance with previous cases described in the literature. The antiphospholipid syndrome should be considered as a possible pathogenetic process in patients presenting with Addison's disease where the aetiology is not obvious.